Endoscope Image Capture System with Mirrorless Camera - Wei, Li; Burke, John; Benet, Arnau; Aghi, Manish; Gurrola, Jose, II; El-Sayed, Ivan (Journal of Neurological Surgery Part B: Skull Base, 2019)
Modern endoscopic surgery relies on capturing high fidelity images for a multitude of purposes. One method of capturing images involves incorporating infrared and 4 k resolution video in the image capture system. However, the price of such whole image capture systems remains expensive and potentially cost prohibitive for some practitioners. A major need exists for less expensive alternatives. Herein, we introduce a method of using a mirrorless camera for the purposes of an endoscope capture device. This system comprises components that are all readily commercially available. Sample pictures taken by this system are provided and the potential function of mirrorless camera is explored. This image capture system provides reasonable quality images, should be more reasonably affordable and easily implementable in variety of practices, and will help decrease the barriers to producing research in the area of endoscopic surgery.
Keywords: endoscopy; image acquisition; skull base